Helium release from 12Cr18Ni10Ti stainless steel after impact of steady-state glow discharge helium plasma - Glazunov, G.P.; Bondarenko, M.N.; Konotopskiy, A.L.; Garkusha, I.E.; Maznichenko, S.M.; Tarasov, I.K. (Вопросы атомной науки и техники, 2021)
The thermal desorption experiments were carried out to study the process of helium outgassing from the stainless steel 12Cr18Ni10Ti after exposure to a steady state glow discharge (GD) plasma in He atmosphere. The currentvoltage characteristics in different plasma regimes have been measured and estimation of He ions energy has been made. Measurements of He release from the stainless steel probes showed the saturation of probe surface with He after the fluencies of ~ 4⋅10¹⁹ ion/cm². The value of He outgassing strongly depends on the regime of GD plasma: pressure of work gas, discharge voltage, etc. Several maximums, including the maximum at the temperature of 100…150 °C, were registered in the He desorption curves that indicated different He atom states on the surface and in the nearest surface bulk. Physical mechanisms of such He outgassing are discussed.